Peroral endoscopic myotomy with fundoplication (POEM-F) for achalasia: Systematic review and meta-analysis - Harishankar Gopakumar; Eugene Annor; Ishaan Vohra; Iman Andalib; Amy Tyberg; Avik Sarkar; Haroon Shahid; Mine Carames; Juan Carlos Carames; Giovanna Porfilio Gularte; Abed Al-Lehibi; Resheed Alkhiari; et al. (Endoscopy International Open)
Background and study aims: Gastroesophageal reflux (GER) and its long-term sequelae remain a concern following peroral endoscopic myotomy (POEM). POEM with fundoplication (POEM-F) is simultaneous fundoplication via pure natural orifice transluminal endoscopic surgery (NOTES). In this study, we evaluated the efficacy and safety of POEM-F in mitigating post-POEM GER. Methods: We performed a comprehensive electronic database search from January 2008 through June 2024 for studies evaluating outcomes of POEM-F performed for managing post-POEM GER. Pooled proportions were calculated using random-effects models. Heterogeneity was assessed using I2 and Q statistics. Results: We included seven studies comprising 127 patients. Pooled technical success for POEM was 96.90%; 95% confidence interval [CI] 91.40-98.90. Pooled technical success of fundoplication was 92.30%; 95% CI 85.20-96.10. Clinical success in treating achalasia was 96.40%; 95% CI 90.70-98.60. Rate of wrap integrity on follow-up was 84.00%; 95% CI 66.00-93.40. Composite clinical success of POEM-F in mitigating post-POEM GER was 86.20%; 95% CI 73.80-93.20. Mean total procedure duration and fundoplication time was 115.74 minutes; 95% CI 103.53-126.96 and 55.28 minutes; 95% CI 47.35-63.20, respectively. The overall pooled major adverse events (AE) rate was 3.60%; 95% CI 1.40-9.40. Conclusions: POEM-F is an effective procedure with an acceptable AE rate in expert hands. It appears to offer clinical benefit in mitigating post-POEM GER. However, further standardization for evaluating clinically significant post-POEM GER and long-term benefit of POEM-F is warranted.